If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (15 + -1x) * 4 = 10 Reorder the terms for easier multiplication: 4(15 + -1x) = 10 (15 * 4 + -1x * 4) = 10 (60 + -4x) = 10 Solving 60 + -4x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -4x = 10 + -60 Combine like terms: 60 + -60 = 0 0 + -4x = 10 + -60 -4x = 10 + -60 Combine like terms: 10 + -60 = -50 -4x = -50 Divide each side by '-4'. x = 12.5 Simplifying x = 12.5
| (15-x).4=10 | | (15-x)84=10 | | 2(2x-5)+x=20-x | | 5x^4+31x^3+66x^2+52x+8= | | 12/45 | | 4(4-k)+30(k-4)=1 | | (2x-8)/6=9 | | 10x+1=9x+7 | | 15/3-4 | | 29x+5y=3 | | 12x+2=3(2x+1)-x+9 | | x+23=4x+17 | | (9y2-1/2z2)2 | | x+23=4x+7 | | (2*2)x=-5 | | 1/2(4x-3)(8x)=0 | | 36(x-3)=4 | | -8x+16=10x+70 | | 6+g=9 | | -4x+4=1 | | 800/400= | | x*x+5x=14 | | 2m+6+6+10m+100= | | 2(4x+3)-5x=18 | | 4x+4x^2+1= | | 4-2(3x-5)-5x=4-(4-2x) | | 3(x-6)-2=-2x+6 | | y+(-6)=20 | | (X/7)=8 | | 4(2x-25)=-124 | | 7/32=14/x | | 7/32=14/× |